Effect of resin pre-coating method on repairing subsurface micro-defects in sandstone and granite. (20th December 2020) - Han, Xiangyu; Liu, Wen; Zhang, Quan; Chen, Yi; Hu, Xiaozhi; Xiao, Qinghua; Chen, Shougen
Highlights: Subsurface micro-defects were repaired with Resin Pre-coating method. The efficiency of Resin Pre-coating was tested with different materials. The effectiveness of Resin Pre-coating is proven to be relevant with grain size. The fracture process provided a new perspective for repair work. Abstract: Subsurface micro-defects in rock and concrete-like materials, crucial for the integrity and durability of the epoxy repaired structures, which should be carefully treated during repair. In this study, a Resin Pre-coating (RPC) method was used to seal the subsurface micro-cracks by capillary action. The sandstone (the average grain size G = 0.5 mm) and granite (G = 2 mm) were selected to test the efficiency of RPC method. After the notched three-point-bending (3-p-b) specimens were loaded to fracture, the substrates were bonded together using epoxy adhesive or epoxy adhesive plus RPC. By comparing the peak loads, fracture energy, crack paths, micro-cracking activities before peak load and X-ray Microscopy (XRM) images of subsurface micro-structures of specimens repaired with different methods, the RPC method was proved to be effective for repairing the subsurface micro-cracks and strengthening the repaired structures, meanwhile the efficiency was confirmed to be relevant with the grain size.